Multilocus Genotyping of Giardia duodenalis in Alpine Musk Deer (Moschus chrysogaster) in China - Cui, Zhaohui; Wang, Qilin; Huang, Xiyao; Bai, Jiayi; Zhu, Bingyang; Wang, Bingchen; Guo, Xiaohang; Qi, Meng; Li, Junqiang (Frontiers in Cellular and Infection Microbiology, 2022)
Giardia duodenalis is the underlying cause of a significant number of outbreaks of gastrointestinal illness in humans and animals worldwide. The purpose of this study was to elucidate the prevalence and genetic diversity of G. duodenalis in captive alpine musk deer (Moschus chrysogaster) in China. A total of 202 fecal samples were collected from three farms in Gansu Province, China. Identification of G. duodenalis was conducted by nested PCR targeting the genes coding for SSU rRNA, β-giardin (bg), glutamate dehydrogenase (gdh) and triosephosphate isomerase (tpi). The overall prevalence of G. duodenalis in captive alpine musk deer in surveyed area was 19.3% (39/202). Two G. duodenalis genetic assemblages were identified, namely assemblage A and E. Mixed genotype infections (A+E) were found in 15.4% (6/39) of positive samples. Multilocus genotyping (MLG) analysis of G. duodenalis isolates revealed six novel assemblage A MLGs formed by two newly-described MLG-subtypes which belonged to sub-assemblage AI. To the best of our knowledge, this is the first report on MLG of G. duodenalis isolates in captive alpine musk deer in China. The presence of zoonotic assemblages and sub-assemblages of G. duodenalis in deer species suggests that these animals may potentially act as a reservoir of this protozoan for humans.